Two‐phase clustering algorithm with density exploring distance measure. Issue 1 (29th March 2018) - Ma, Jingjing; Jiang, Xiangming; Gong, Maoguo
Abstract : Here, the authors propose a novel two‐phase clustering algorithm with a density exploring distance (DED) measure. In the first phase, the fast global K ‐means clustering algorithm is used to obtain the cluster number and the prototypes. Then, the prototypes of all these clusters and representatives of points belonging to these clusters are regarded as the input data set of the second phase. Afterwards, all the prototypes are clustered according to a DED measure which makes data points locating in the same structure to possess high similarity with each other. In experimental studies, the authors test the proposed algorithm on seven artificial as well as seven UCI data sets. The results demonstrate that the proposed algorithm is flexible to different data distributions and has a stronger ability in clustering data sets with complex non‐convex distribution when compared with the comparison algorithms.